Crystal Structure Refinement, Magnetic and Mössbauer Analysis of LaFeO3 Perovskite Synthesized by SOL-GEL method (Bangladesh Journal of Physics, 2022)
In this present study, LaFeO3 nanoparticles have been successfully synthesized by sol-gel method and annealed the produced sample at 600 °C, 800 °C, 1000 °C, 1200 °C. The influence of annealing temperature on the structural, morphological and magnetic properties of the developed nanoparticles has been investigated systematically. The XRD patterns confirmed the absence of impurity or secondary phase in the spectra. Orthorhombic crystal system of pbnm space group was successfully determined by Rietveld refinement. Scherrer method was used to calculate crystallite size. An increasing trend in crystallite size and improving crystallinity were obtained with increasing annealing temperature. Scanning Electron Microscopy (SEM) images showed a homogeneous distribution of increasing average particle sizes ranging from 35 nm to 450 nm. Magnetic hysteresis (M-H) loop was recorded at room temperature revealed weak ferromagnetism in nanocrystalline lanthanum ferrite. The maximum magnetization was found to be 1.82 emu/g at 600 °C, and it was sharply decreased to 0.33 emu/g at 1200 °C annealing temperature. Interactions between the antiferromagnetic and ferromagnetic exchange coupling are influenced by the uncompensated spin canting causes to accomplish the ordering of weak ferromagnetism in LaFeO3. Moreover, the bond length of Fe-O and the bond angle of Fe-O-Fe were decreased with decreasing annealing temperature. As a result, Fe ions, come closer to each other, enhancing the ferromagnetic exchange interaction between iron ions via oxygen ions made significant contributions to the magnetic properties of LaFeO3 nanoparticles. Mössbauer spectroscopy was used to find the nature of interactions for the observed magnetic behavior depending on different site environments with varying annealing temperatures.Bangladesh Journal of Physics, 27(2), 27-37, December 2020